2017
DOI: 10.3390/w9060433
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Anionic Surfactant on Saturated Hydraulic Conductivity of Loamy Sand and Sandy Loam Soils

Abstract: Surfactants released into the terrestrial environment in large amounts can potentially alter the physical, chemical and biological properties of soils, particularly the saturated hydraulic conductivity (K s ). Unfortunately findings regarding this process are quite limited. In this study, column tests were used to analyze the effects of Aerosol 22, a widely used anionic surfactant, on K s of loamy sand and sandy loam soils. Solutions were injected into columns from the bottom with controlled pressure heads. Bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…This low permeability value of the colmation layer is the result of soil pores being clogged by the organic compound, the surfactant Aerosol 22. The formation of a colmation layer and soil pore clogging were reported in a study investigating the effect of anionic surfactant Aerosol 22 on saturated hydraulic conductivity of these same loamy sand (Sparta and Gilford series) and sandy loam (Lewsiton and Greenson series) soils (Peng et al., 2017). In addition, as the soil columns underwent slicing, the crystallization of the surfactant in soil was observed in the top soil layer.…”
Section: Discussionmentioning
confidence: 84%
“…This low permeability value of the colmation layer is the result of soil pores being clogged by the organic compound, the surfactant Aerosol 22. The formation of a colmation layer and soil pore clogging were reported in a study investigating the effect of anionic surfactant Aerosol 22 on saturated hydraulic conductivity of these same loamy sand (Sparta and Gilford series) and sandy loam (Lewsiton and Greenson series) soils (Peng et al., 2017). In addition, as the soil columns underwent slicing, the crystallization of the surfactant in soil was observed in the top soil layer.…”
Section: Discussionmentioning
confidence: 84%
“…Soil EC in this area is highly affected by the discharge of industrial effluents as it dissolves salts in the soil and found to be in the same range in the sites as shown in table 2. High concentration of EC in soil causing excessive particles to wash away from the soil due to decline surface tension, large pores and a high EC in the soil will allow more pollutants to enter the soil, resulting in increased groundwater pollution [16,49]. These research in the line with the [16] who indicated that Soil irrigation with a detergent effluent would raise the electrical conductivity (EC) of the soil, which increases salinity of soil in the long time.…”
Section: Soil Chemical Properties Affected By Industrial Effluentsmentioning
confidence: 97%
“…Due to their massive consumption in various industries and households, a relatively high concentration of surfactants is reported in sediments (Li et al, 2018), surface waters (D'Agostino & Mabury, 2017; Munoz et al, 2017), soil and sludge (Abril et al, 2020; Gomez et al, 2011; Jardak et al, 2016). As a component of greywater, surfactants have been identified to cause water repellence and a decrease in the hydraulic conductivity of soil (Lado & Ben‐Hur, 2009; Peng et al, 2017; Travis et al, 2010). Increased foaming of the water bodies and changes in several physicochemical properties of soil are two major effects of the surface‐active agents on the abiotic environment.…”
Section: Surfactant Pollution In Abiotic and Biotic Componentsmentioning
confidence: 99%
“…Alteration in the optimum soil pH will pose a threat to the soil's biological activity (Anwar, 2011; Chirani et al, 2021). In a study to investigate the effects of common household surfactants on hydraulic conductivity, sorptivity, penetration and soil stability, it was observed that the application of surfactants resulted in a reduction in hydraulic conductivity (Abu‐Zreig et al, 2003; Peng et al, 2017). Also, the magnitude of hydraulic conductivity is dependent on the soil texture, type of surfactant and concentration.…”
Section: Surfactant Pollution In Abiotic and Biotic Componentsmentioning
confidence: 99%